AD-DAKHÎL” DALAM KITAB AL-KASYFU WA AL-BAYÂN ‘AN TAFSÎR AL-QUR’ÂN KARYA IMAM AŠ-ŠA’LABIY W. 427 H - Khoirun Niat (AN NUR: Jurnal Studi Islam, 2013)
The research is about “ad-Dakhîl” in Imam’s Tafsir aš-Ša’labiy (Al-Kasyfu wa Al-Bayân ‘an Tafsîr Al-Qur’ân) beginning of al-Qa?a? until Saba`. The study has two research focuses, namely (1) to know the concept of ad-Dakhil, and (2) to know the cases of ad-Dakhil in Tafsir as-Tsa’labi taken from al-Qashas into Saba`. The Study employed a descriptive qualitative approach. The source of the data was verses of Koran taken from al-Qashas into Saba` in al- Kasyf wa al-Bayan ‘An Tafsir al-Qur’a, while the source sekunder’s data taken from references else. Sekunder’s data used helped for to analyze primer data. Data could been library reseach method. The results of the study are presented as follows. First, ad-Dakhil can be defined as a prior interpretation in explaining the meaning of the verses of Koran. Consequently, it will give a false description of Islam. Second, there are 67 cases of ad-Dakhil which can be found in al- Kasyf wa al-Bayan ‘An Tafsir al-Qur’an taken from al-Qashas until Saba`. The big amount of the cases of ad-Dakhil implies that Tafsir Tsa’labi contains many invalid stories (riwayat) which can’t be used to interpret the meaning of the verses of Koran.